SETTING A NEW LEGAL FRAMEWORK FOR INTEGRATION OF PACIFIC ALLIANCE - Ugarte Vega Centeno, Máximo Alfredo (2015)
Initiatives negotiating regional agreements and bilateral free trade negotiations, have become a feature of the current international economic relations and Latin America could not be excluded. It is in this direction that from the nineties arise many more regional or subregional agreements among these is the initiative of the Pacific Alliance puts a touch of pragmatic and commercial distinction in relation to other regional or subregional agreements, including the international stage new elements of reflection for the integration process in Latin America.